2022
DOI: 10.4103/jhrs.jhrs_103_21
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Levels in Trophectodermal Cells Show No Association with Blastocyst Development and Pregnancy Outcomes

Abstract: Background: In patients undergoing assisted reproduction, levels of mitochondrial DNA (mtDNA) in the trophectodermal cells of the developing blastocyst are suggested to be associated with its ability to implant. However, discrepancies exist regarding the use of mtDNA levels as a reliable biomarker to predict outcomes of assisted reproduction. Aims: The aim of the study is to explore the association of trophectodermal mtDNA levels to determine blastocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A better understanding of mtDNA kinetics in pre-implantation embryos is particularly relevant because the mtDNA copy number has been considered as a potential marker of human embryo quality [ 46 , 47 ]. Associations between the embryo mtDNA copy number and implantation potential have been uncovered in some studies but not others [ 48 , 49 , 50 , 51 , 52 , 53 ]. Importantly, mtDNA is measured in TE biopsies, which our preclinical data confirmed is not necessarily reflective of the mtDNA copy number within the ICM but may be important for successful implantation.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of mtDNA kinetics in pre-implantation embryos is particularly relevant because the mtDNA copy number has been considered as a potential marker of human embryo quality [ 46 , 47 ]. Associations between the embryo mtDNA copy number and implantation potential have been uncovered in some studies but not others [ 48 , 49 , 50 , 51 , 52 , 53 ]. Importantly, mtDNA is measured in TE biopsies, which our preclinical data confirmed is not necessarily reflective of the mtDNA copy number within the ICM but may be important for successful implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in multiple clinics found that high mtDNA levels in blastocysts were related to aneuploidy embryos and implantation failure ( 216 218 ). The latest retrospective investigation analyzed the transfer cycle of frozen single euploid embryos, and the results showed that no correlation was observed between mtDNA content and blastocyst morphology grades or pregnancy outcomes ( 219 , 220 ). Still, lower mtDNA content was associated with delayed blastocyst development ( 219 ).…”
Section: Focus On Mitochondria Of Human Oocyte During Assisted Reprod...mentioning
confidence: 99%
“…Still, lower mtDNA content was associated with delayed blastocyst development ( 219 ). It should be noted that there is currently no consensus on the threshold for the mtDNA copy number of blastocysts, and the accuracy of using mtDNA copy number as a single predictive biomarker for embryo selection and developmental potential remains low ( 216 220 ).…”
Section: Focus On Mitochondria Of Human Oocyte During Assisted Reprod...mentioning
confidence: 99%
“…Consequently, studies reported that embryos with mtDNA levels higher than average showed a poor implantation rate ( Diez-Juan et al , 2015 ; Fragouli et al , 2015 ). However, confirmatory studies from other groups failed to validate the initial findings and suggested that mtDNA cannot predict the reproductive potential of embryos ( St John, 2016 ; Treff et al , 2017 ; Ritu et al , 2022 ). Furthermore, a review by Seli has concluded that mtDNA copy number (mtCN) may be used as a biomarker for embryo viability ( Seli, 2016 ).…”
Section: Introductionmentioning
confidence: 99%